Rhinologic manifestations of Burkitt Lymphoma in a pediatric population: Case series and systematic review. (June 2019) - Hong, Xinyuan; Khalife, Sarah; Bouhabel, Sarah; Bernard, Chantal; Daniel, Sam J.; Manoukian, John J.; Nguyen, Lily H.P.
Abstract: Introduction: Burkitt lymphoma (BL), an aggressive form of B-cell non-Hodgkin's lymphoma, arising from the nose and paranasal sinuses is relatively rare. It can present with various symptoms leading to potential misdiagnosis and delayed treatment. BL is fatal if left untreated, while early identification and treatment can improve prognosis. Objectives: 1) To review clinical presentations and sites of involvement of six cases of pediatric BL with rhinologic manifestations and compare these with the current literature. 2) To raise awareness on the variety of presentations of BL in this particular anatomic location. Methods: A series of six cases of pediatric (0–18 years) BL with rhinologic manifestations is presented. Age, sex, ethnicity, symptoms, imaging, staging, treatment and outcome were recorded. A systematic review of literature was also conducted using PRISMA guidelines. The search strategy used keywords related to rhinologic manifestations of BL (nasal cavity, nasopharynx, paranasal sinus etc.; Burkitt etc.) and included studies published in English and French describing patients 0–18 years of age. Results: 42 patients were included (six from case series and 36 from current literature). Most common presenting symptoms were: nasal obstruction (29%), facial swelling (24%), headache (21%) and proptosis (19%). Most frequent sites of presentation were: nasopharynx (40%), maxilla (40%) and sphenoid (33%). More than half (60%) had systemic involvement, of which the most common locations were: kidney (19%), pancreas (17%) and liver (17%). Mortality from BL in children from this study population was correlated with a longer duration of symptoms prior to presentation, as well as a misdiagnosis preceding the final diagnosis of BL. Conclusions: This study brings understanding to the numerous presentations of the same aggressive disease, promotes high clinical suspicion when evaluating common otolaryngologic symptoms and can guide healthcare providers in diagnosing pediatric BL with rhinologic manifestations.